2020
DOI: 10.1371/journal.pone.0233233
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-visit blood pressure variability and risk of chronic kidney disease: A systematic review and meta-analyses

Abstract: Previous studies have shown that visit-to-visit blood pressure variability (BPV) is associated with chronic kidney disease (CKD). However, the results have not been consistent among studies. This systematic review and meta-analysis was conducted to comprehensively assess the association between visit-to-visit BPV and the risk of CKD. MethodsMedline, Embase, and the Cochrane Library were searched from the date of inception through 1 August 2019 using the terms "blood pressure variability," "chronic kidney disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Several longitudinal studies have reported that higher BPV was significantly associated with the risk of developing CKD or progression to end‐stage kidney disease, but most of these assessments were made using visit‐to‐visit BPV based on office blood pressure. 8 , 9 , 10 , 11 , 12 A longitudinal study by Okada et al 23 did not reveal a significant association between BPV based on home blood pressure and incidence of end‐stage kidney disease over 3 years in 135 patients with CKD. Discrepancies between these studies and our present results may be attributable to differences in the study subjects (ie, a general population versus patients with CKD), sample size (ie, 2432 versus 135), and outcomes (ie, incident CKD versus incident end‐stage kidney disease).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several longitudinal studies have reported that higher BPV was significantly associated with the risk of developing CKD or progression to end‐stage kidney disease, but most of these assessments were made using visit‐to‐visit BPV based on office blood pressure. 8 , 9 , 10 , 11 , 12 A longitudinal study by Okada et al 23 did not reveal a significant association between BPV based on home blood pressure and incidence of end‐stage kidney disease over 3 years in 135 patients with CKD. Discrepancies between these studies and our present results may be attributable to differences in the study subjects (ie, a general population versus patients with CKD), sample size (ie, 2432 versus 135), and outcomes (ie, incident CKD versus incident end‐stage kidney disease).…”
Section: Discussionmentioning
confidence: 96%
“… 5 , 6 , 7 Several epidemiological and clinical studies have reported that elevated visit‐to‐visit BPV assessed by office blood pressure at each visit was associated with increased risk of the incidence or progression of CKD. 8 , 9 , 10 , 11 , 12 Alternatively, the assessment of BPV based on home blood pressure, which is reproducible and has no white coat effect, might provide reliable information on BPV, and could lead to optimization of blood pressure management. 3 , 13 , 14 , 15 Home blood pressure measurements can be performed under standardized conditions, allowing home blood pressure values to be used to monitor blood pressure variability over several days.…”
mentioning
confidence: 99%
“…Chen et al demonstrated that even after adjusting for mean childhood BP levels, adult hypertension was associated with increased BPV in terms of SD of serial BP measurements obtained during childhood [ 44 ]. It was reported that both high BP-SD and BP-CV might increase the risk of chronic kidney disease, but the former association was more significant [ 45 ]. One meta-analysis provided evidence that great SBP-SD may indicate an increased risk of stroke (RR 1.20, 95% CI 1.07–1.35); however, when CV was considered, the hazard for stroke was not stable (RR 1.12, 95% CI 1.00–1.26) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In hemodialysis patients, some studies documented that BPV was related to cardiovascular, cerebrovascular and all-cause death ( 10 , 11 ). However, in CKD patients who do not yet require dialysis, the influence of BPV on renal disease and its value in determining long-term prognosis remains to be elucidated ( 12 ). For patients with stage 1–4 CKD, it is of great importance to protect residual renal function, delay the need for renal replacement therapy, reduce the occurrence of CVD, and improve the prognosis.…”
Section: Introductionmentioning
confidence: 99%